2004
DOI: 10.3136/fstr.10.290
|View full text |Cite
|
Sign up to set email alerts
|

6-Methylsulfinylhexyl Isothiocyanate, an Antioxidant Derived from Wasabia japonica MATUM, Ameliorates Diabetic Nephropathy in Type 2 Diabetic Mice

Abstract: Many studies have examined the protective effects of antioxidative agents against diabetic nephropathy, using various models. 6-Methylsulfinylhexyl isothiocyanate (6-MSITC) isolated from wasabi (Wasabiajaponica MATUM) induces glutathione S-transferase in vitro, thus 6-MSITC may act as an antioxidant in vivo. The aim of this study was to examine whether wasabi powder (WP) and 6-MSITC suppress oxidative stress in vivo and inhibit the impairment of renal function and diabetic nephropathy, using type 2 diabetic mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
(33 reference statements)
0
22
0
1
Order By: Relevance
“…6-Methylsulfinylhexyl ITC (hesperin), an ITC isolated from wasabi (Wasabia japonica), protected from oxidative stress and ameliorated renal dysfunction in type 2 diabetic mice. In this study, KK-Ay type 2 diabetic mice were fed CRF-1 containing 0.03% hesperin for 4 weeks: there was statistically no difference in TBARS, however, urinary 8hydroxy-2 0 -deoxyguanosine (8-OHdG), one of the markers of oxidative stress tended to be lower in the hesperin group than in the control group [Fukuchi et al, 2004]. Unlike N-acetylcysteine (NAC) that produced no improvement, phenethyl ITC 0.5% added to drinking water for 4 weeks effectively lowered oxidative-stressmediated testicular toxicity, induced by coadministration of acrylamide 0.02%, in male Sprague-Dawley rats .…”
Section: Indirect Antioxidant Activity Of Itcsmentioning
confidence: 84%
“…6-Methylsulfinylhexyl ITC (hesperin), an ITC isolated from wasabi (Wasabia japonica), protected from oxidative stress and ameliorated renal dysfunction in type 2 diabetic mice. In this study, KK-Ay type 2 diabetic mice were fed CRF-1 containing 0.03% hesperin for 4 weeks: there was statistically no difference in TBARS, however, urinary 8hydroxy-2 0 -deoxyguanosine (8-OHdG), one of the markers of oxidative stress tended to be lower in the hesperin group than in the control group [Fukuchi et al, 2004]. Unlike N-acetylcysteine (NAC) that produced no improvement, phenethyl ITC 0.5% added to drinking water for 4 weeks effectively lowered oxidative-stressmediated testicular toxicity, induced by coadministration of acrylamide 0.02%, in male Sprague-Dawley rats .…”
Section: Indirect Antioxidant Activity Of Itcsmentioning
confidence: 84%
“…In Japan, wasabi is used as a spice or as pickles due to its strong pungent constituents, including isothiocyanates such as allyisothiocyanate. Previous studies have reported on antimicrobial [9], antioxidative [10] and anti-carcinogenic activities [11] of isothiocyanate. However, few studies have examined the functional properties of other components in wasabi, particularly in its summer leaves, which are considered late-growth and have little pungency [12].…”
Section: Introductionmentioning
confidence: 99%
“…According to other studies, Wasabi leafstalk extract stimulates bones calcification and it might be used in osteoporosis prevention (Suzuki et al, 1997;Suzuki and Masayoshi, 2004;Yamaguchi, 2016). 6-methylsulfinylhexyl isothiocyanate isolated from Wasabi has positive antioxidant effects in diabetes renal dysfunction (Fukuchi et al, 2004). The research also shows a possible use of transgenesis of a wasabi gene; in potatoes, the wasabi gene has a positive role in partial resistance to Botrytis cinerea (gray mold) (Khan et al, 2006).…”
Section: Introductionmentioning
confidence: 86%